Comparative Study of Ethylene Catalytic Aromatization and Adsorption Onto Two Kinds of Molecular Sieves - Ma, Xiaodong; Ouyang, Feng; Shen, Dongmei; Cao, Xiaokai (Asian Journal of Chemistry, 2012)
The catalytic aromatization and adsorption of ethylene onto two kinds of molecular sieves was investigated at different temperatures. The adsorption amount of ethylene did not decrease with the increasing temperature all the time. By in situ FTIR of pyridine adsorption, NH3-TPD and GC-MS a possible mechanism was proposed. The acid sites of molecular sieves would become the active sites for aromatization of ethylene to improve the adsorption capacity under high temperature. The maximum adsorption amount was proportional to the number of the acid sites activated by high temperature. Final adsorbates were mainly aromatics. The sizes of final products were limited to the diameters of pores.